Tingkat pengetahuan mahasiswi Fakultas Keguruan Ilmu Pendidikan Universitas Mataram mengenai menstruasi - Baiq Ayu Wulan Maharani Putri; Candra Eka Puspitasari (Sasambo Journal of Pharmacy, 2023)
Menstruation is a physiological event for female adolescents and menstruation is also an indicator of sexual maturity in female adolescents. This study aims to determine the level of knowledge of female students of the Teaching and Education Faculty of Mataram University regarding menstruation. This research is an observational study with a cross-sectional design. The research instrument was a questionnaire distributed online with students of the students of Teaching And Educational Faculty, at Mataram University as respondents who were then analyzed descriptively. Descriptive analysis was carried out for characteristic data and the knowledge level of respondents. The results of the study in the age range of 17 years to 26 years, the average level of knowledge is greater in the age range of 26 years. This can be influenced by the age factor, the older you are, the more knowledge you will get. Meanwhile, at a high level of knowledge, there were 156 people who were included in that category, 43 people who were included in the sufficient category, and 1 person who was included in the low category. level of knowledge about menstruation in students of the teaching and educational faculty shows that 156 people are included in the high category, 43 people are included in the sufficient category, and 1 person is included in the low category.